Meningkatkan Prestasi Belajar Bahasa Indonesia (Membaca) Melalui Pembelajaran Kelompok (Partisipatif) Siswa Kelas V SDN 004 Rambah Hilir - Rasita Rasita (STKIP Rokania Pasir Pangaraian, 2018)
One of the goals of teaching is to increase knowledge. Teachers must be able to define strata and models of learning. Classroom action research aims to determine whether participatory (group) methods can improve learning outcomes Indonesian reading in grade V SDN 004Rambah Hilir. The formulation of the problem whether with group learning (participatory) can improve the learning achievement of Bahasa Indonesia (read). The subject of this research is done in class V SDN 004Rambah HilirTenelitian consists of four stages of planning, implementation, observation and refleksi.Alat data collection used in the form test in the form of a description. Implementation of the improvement is done two cycles every cycle held two meetings with the completeness cycle I = 73.5% and cycle II = 85%. This research aims to improve student learning outcomes, with the type of qualitative descriptive research it can be concluded that the participatory method can improve learning outcomes Indonesian about reading for students of grade V SDN 004 Rambah Hilir